Some Methodological Guidelines for Contrastive Analysis and Error Analysis - Choi, Kim Yok (Journal of Modern Languages, 2017)
This article offers some guidelines in the methods used and the steps to follow in conducting research in contrastive analysis (CA) and error analysis (EA). The paper also shows that, besides observing their classroom performance (oral or written), the researchers can also administer tests specifically designed to obtain information on the learners' interlanguage.